2001
DOI: 10.1128/aem.67.9.4199-4205.2001
|View full text |Cite
|
Sign up to set email alerts
|

Fate ofMycobacterium aviumsubsp.paratuberculosisin Swiss Hard and Semihard Cheese Manufactured from Raw Milk

Abstract: Raw milk was artificially contaminated with declumped cells of Mycobacterium avium subsp. paratuberculosis at a concentration of 10 4 to 10 5 CFU/ml and was used to manufacture model hard (Swiss Emmentaler) and semihard (Swiss Tisliter) cheese. Two different strains of M. avium subsp. paratuberculosis were tested, and for each strain, two model hard and semihard cheeses were produced. The survival of M. avium subsp. paratuberculosis cells was monitored over a ripening period of 120 days by plating out homogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 25 publications
2
64
1
2
Order By: Relevance
“…No previous study has shown the impact of culture medium on acid or thermal resistance of M. paratuberculosis. The study of Spahr and Schafroth investigating M. paratuberculosis survival in cheese used Middlebrook 7H9-OADC medium supplemented with 0.5% (vol/vol) glycerol (34). The thermal resistance of M. paratuberculosis had been previously reported but with widely different results for growth of the organism in different types of medium such as 7H9 medium (35), 7H9-ADC medium (30), 7H9-OADC medium (19,36,37), 7H9-OADC medium supplemented with 0.5% (vol/vol) glycerol (13), and WR-GD medium (18).…”
Section: Discussionmentioning
confidence: 99%
“…No previous study has shown the impact of culture medium on acid or thermal resistance of M. paratuberculosis. The study of Spahr and Schafroth investigating M. paratuberculosis survival in cheese used Middlebrook 7H9-OADC medium supplemented with 0.5% (vol/vol) glycerol (34). The thermal resistance of M. paratuberculosis had been previously reported but with widely different results for growth of the organism in different types of medium such as 7H9 medium (35), 7H9-ADC medium (30), 7H9-OADC medium (19,36,37), 7H9-OADC medium supplemented with 0.5% (vol/vol) glycerol (13), and WR-GD medium (18).…”
Section: Discussionmentioning
confidence: 99%
“…The two most important factors contributing to the inactivation of bacterial pathogens during the 60-day curing process are low pH and high salt concentration (Spahr and Schafroth, 2001).…”
Section: Map In Cheesementioning
confidence: 99%
“…This is mainly due to the detection of IS900-positive mycobacteria in tissues of Crohn's disease patients (9) and the observation of an extraordinary temperature resistance resulting in M. paratuberculosis not being fully inactivated by pasteurization temperatures (13,33) and surviving the cheese-manufacturing process (30).…”
mentioning
confidence: 99%